2017
DOI: 10.1007/s11625-017-0449-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the food security outcomes of industrial crop expansion in smallholder settings: insights from cotton production in Northern Ghana and sugarcane production in Central Ethiopia

Abstract: The current industrial crop (IC) expansion in Sub-Saharan Africa (SSA) may have important ramifications for food security. This study proposes a rapid appraisal method that can capture the food security outcomes of IC expansion in smallholder settings in SSA. A key element of this approach is a common unit of household caloric intake that captures food security across its four pillars (availability, access, utilization, stability). This approach also considers the role of women in household food security. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…However, consequences are not always positive particularly for the poor; and diverging outcomes have been observed for different community groups. For example, the cash crop sugarcane was found to have a positive effect on food security in Ethiopia, but cotton production in Ghana resulted in lower food security among growers (Lam et al 2017). In Sulawesi, Indonesia, Belsky and Siebert (2003) found that food self-sufficiency would likely decline with conversion of food-crop focused swidden fields to cocoa farms.…”
Section: Background On the Relationships Between Livelihoods And Foodmentioning
confidence: 99%
“…However, consequences are not always positive particularly for the poor; and diverging outcomes have been observed for different community groups. For example, the cash crop sugarcane was found to have a positive effect on food security in Ethiopia, but cotton production in Ghana resulted in lower food security among growers (Lam et al 2017). In Sulawesi, Indonesia, Belsky and Siebert (2003) found that food self-sufficiency would likely decline with conversion of food-crop focused swidden fields to cocoa farms.…”
Section: Background On the Relationships Between Livelihoods And Foodmentioning
confidence: 99%
“…Relying on multiple metrics is essential for multi-dimensional concepts such as food security [31], with such standardized metrics being increasingly used to assess food security impacts in industrial crop settings of SSA (e.g., [32][33][34][35]). Essentially such approaches can reduce the complexity (and increase the consistency) of food security assessments considering the multiple interacting mechanisms that that are often at play in such industrial crop settings of SSA, for example, [1,8,9,36].…”
Section: Data Collectionmentioning
confidence: 99%
“…The recent surge in large-scale land acquisitions for industrial crops in SSA [5] has raised concerns about the effects of large-scale industrial crop expansion on local food security and rural livelihoods [6,7]. However, it is not always clear as to what extent (and under which conditions) industrial crop production improves or compromises rural livelihoods and household food security in SSA [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…They discuss a transdisciplinary approach that allows the establishment of linkages between the local communities that are in dire need of climate change adaptation interventions in northern Ghana and regional/national stakeholders. Dam et al (2017) develop a rapid appraisal methodology for assessing the local food security outcomes of industrial crop expansion in smallholder settings of Africa. They develop a metric of household caloric intake that captures food security across its four pillars (i.e., availability, access, utilization, stability), but also considers gender roles, and especially the toll that unpaid household work can take on household food security.…”
Section: Aims and Structure Of The Special Featurementioning
confidence: 99%